INTERPERSONAL SKILLS FOR ENGINEERING STUDENTS: TEACHING STRATEGIES - V M , Chithra; L R , Anitha (International Journal of Psychosocial Rehabilitation, 2020)
Skill is an ability to utilize one‟s knowledge to acquire set of traits for a better living. Talent is also an ability in which the acquired is honed and mastered. There are various kinds of skills among which interpersonal skills plays a major role in a student‟s life and career. Interpersonal skill is a type of ability through which people interact, inter-relate and react with others in all walks of life. It is the need of the hour that every student must possess this great skill to the optimum level to shine bright personally, academically, socially and economically. Overall growth of a student is determined by the way one relates himself/herself with the society that he/she is exposed to. Teaching interpersonal skills for students has become an indispensable act of an English teacher. This paper envisages the various teaching strategies that English teachers can utilize to impart this great life skill among the Engineering students.